Severe Colitis in 2 Patients with Melanoma Treated with BRAF/MEK Inhibitors: Case Report and Literature Review - Chloe Wautier; Jolanta Gourmaud; Catherine Dong; Gregoire Berthod (Case Reports in Oncology, 2024)
Introduction: Encorafenib and binimetinib, a combination of BRAF and MEK inhibitors, is a standard of care for patients with advanced BRAFV600-mutant melanoma. This combination is known to have gastrointestinal side effects, most of which are mild and managed symptomatically. However, very few studies have reported severe colitis. Case Presentation: We report here 2 patients with advanced melanoma who developed severe ulcerated right colitis manifested by diarrhea and hematochezia while being treated with encorafenib and binimetinib after immune checkpoint therapy. Conclusion: This rare but serious adverse event was not described in early phase 3 trials but has emerged in recent years, particularly with the sequential use of immune checkpoint inhibitors followed by BRAF/MEK inhibitors. In a comprehensive review of the existing literature, we identified 20 cases of severe colitis due to BRAF/MEK inhibitors. Clinical, endoscopic, and histological features are described to provide insight into the current understanding of this poorly understood clinical entity.